Dispute resolution in NAFTA and the WTO: a useful guide for SADC? - Snyman-Van Deventer, E. (Faculty of Law, University of the Free State, 2003)
In the process of developing, structuring and formalising the mechanism for settlement of trade disputes in the SADC region, the system for the settlement of disputes in both NAFTA and the WTO can serve as a useful guide for SADC and even more so for the African Union. The swift, fair and just settlement of especially trade disputes will be a major factor in the economic development of the region and it is therefore necessary that a mechanism for the settlement of disputes is established that will serve the aims of SADC and its member states. This article provides an overview of the mechanisms for trade dispute resolution in the WTO and NAFTA as guide for SADC.

In die proses van die ontwikkeling, strukturering en formalisering van die metodes van handelsgeskilbeslegting in die SAOG streek, kan die stelsel vir geskilbeslegting in beide NAFTA en die WHO as handige riglyne dien vir SAOG en selfs meer nog ook vir die Afrika Unie. Die vinnige, billike en regverdige beslegting van veral handelsgeskille sal 'n belangrike faktor in die ekonomiese ontwikkeling van die streek speel en dit is derhalwe noodsaaklik dat 'n stelsel vir die beslegting van geskille daargestel word wat die oogmerke van die SAOG en die lidlande sal dien. In hierdie artikel word 'n oorsig gegee van die stelsel van geskilbeslegting in NAFTA en die WHO as riglyn vir SAOG.